Immunopathology of emerging and re-emerging viral infections: an updated overview - Dimpu Gogoi; Pranjal Jyoti Baruah; Kanwar Narain (Acta Virologica, 2024)
Humankind has witnessed increased frequency of emerging and re-emerging viral diseases in the past few decades. The major categories of pathogenic emerging and re-emerging viral infections include respiratory, arthropod-borne and bat-borne zoonotic viruses. These viral infections are notorious for causing immune dysregulation and have the potential to mount excessive immune reaction, causing immunopathology that includes tissue injury, systemic inflammation, multi-organ failure and even death. A better understanding of the emerging or re-emerging viral-mediated immunomodulation is necessary for controlling the virus, while preventing severity of the disease associated with exaggerated immune response. In this article, we review the current understanding of emerging and re-emerging respiratory, arboviral and bat-borne zoonotic viruses; and consequent immune dysregulation or immunopathology associated with these viral infections.